Residue Behavior of Methoxyfenozide and Pymetrozine in Chinese Cabbage and Their Health Risk Assessment - Wenting Wang; Yu-Jin Cho; Jong-Wook Song; Yeong-Jin Kim; Jong-Su Seo; Jong-Hwan Kim (Foods, 2022)
Methoxyfenozide and pymetrozine are used for pest control in the cultivation of Chinese cabbage. This has raised concerns in recent years due to health risks. Therefore, this study aimed to determine the residual concentrations of pesticides in the target crop and associated health risks. The dynamics and influence of environmental factors on the dissipation of methoxyfenozide and pymetrozine residues in Chinese cabbage were investigated. Analyses were performed using a modified QuEchERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) and an optimized high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The observed half-lives of methoxyfenozide and pymetrozine in cabbage samples ranged between two sampling seasons: in May–June, half-lives of methoxyfenozide and pymetrozine were 1.20 days and 1.89 days, respectively; during October–November, half-lives of methoxyfenozide and pymetrozine were 11.8 and 2.80 days, respectively. Meanwhile, a negative Spearman correlation was found between the residual concentrations and temperature (p < 0.01). This indicates that higher temperatures resulted in higher dissipation rates for methoxyfenozide and pymetrozine, suggesting that these pesticides degraded faster at higher temperatures. Additionally, higher pesticide residues in Chinese cabbage during low-temperature seasons resulted in higher risk quotients (RQ) (RQ > 1) for both analyzed compounds, which suggests that the effect of temperature on pesticide degradation needs to be considered as an essential factor while setting up the maximum residue limits (MRL).